Pengaruh Bauran Pemasaran Terhadap Loyalitas Pasien Rawat Jalan Rumah Sakit TNI AU Lanud EL Tari - Kusuma, Kevin Rizki Agung; Syaodih, Erliany; Handayani, Nining (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
El Tari Air Force Base Hospital (RS TNI AU Lanud El Tari) is one of the health facilities in Kupang City, NTT Province with the status of a Class D Pratama Hospital. RS TNI AU Lanud El Tari has general medical services, emergency services, nursing services, primary laboratory services, radiology services and pharmacy services. However, according to the monthly report from March 2022 to March 2023, the total number of outpatient visits at the RS TNI AU Lanud El Tari was only 843 visits. In fact, in BPJS capitation, family register card that registered at RS TNI AU Lanud El Tari reached 997 families. In this regard, the researcher wants to know more about the influence of the marketing mix on the loyalty of outpatients at the RS TNI AU Lanud El Tari. The research variables include product, place, people, promotion, price, process and physical evidence. The population in this study were 843 outpatient polyclinic patients visiting the RS TNI AU Lanud El Tari in 2022 - 2023. Data was collected through a validated questionnaire that performed using the SPSS Test. The results of this research are: product, process and physical evidence have a significant relationship with patient loyalty to outpatient services at the RS TNI AU Lanud El Tari. Meanwhile, place, people, promotion and price do not have a significant relationship with patient loyalty in outpatient services at the RS TNI AU Lanud El Tari.